2019
DOI: 10.1590/1678-4162-10602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatotropin on survival and diameter of bovine preantral follicles

Abstract: The aim of this study was to evaluate the effect of Recombinant bovine somatotropin (rbST) on survival and diameter of bovine preantral ovarian follicles (PAOF) cultured in vitro. Ovaries were collected from adult cows and fragments of ovarian cortex were immediately fixed (non-cultured control) or cultured in vitro in α-MEM+ alone or containing 10, 50, 100 or 1,000ng/mL rbST. The fragments were processed for Classical Histology and Transmission Electron Microscopy. After one and seven days of culture, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Tcontrol=Control treatment, TrbST=Treatment with rbST, Means lacking a common superscript letter in a row differ by Tukey's test (p<0.05). 2 Tcycling=Treatment with cycling cows, and Tanestrous=Treatment with anestrous cows, 2,3 Means lacking a common superscript letter in the same line differ by Tukey's test (p<0.05). SEM=Standard error of mean…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tcontrol=Control treatment, TrbST=Treatment with rbST, Means lacking a common superscript letter in a row differ by Tukey's test (p<0.05). 2 Tcycling=Treatment with cycling cows, and Tanestrous=Treatment with anestrous cows, 2,3 Means lacking a common superscript letter in the same line differ by Tukey's test (p<0.05). SEM=Standard error of mean…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that rbST stimulates the production of endogenous growth hormone and insulin-like growth factor I (IGF-I), which are crucial for reproduction. In addition, the presence of rbST receptors in the uterus and ovaries has previously been observed [3].…”
Section: Introductionmentioning
confidence: 89%